Efficient anti-sticking agent applied to concrete mechanical equipment as well as preparation method and application of efficient anti-sticking agent

By spraying a highly efficient anti-adhesive agent prepared by emulsion polymerization on the inner wall of the concrete mechanical equipment, a hydrophobic and wear-resistant coating is formed, which solves the problem of adhesion of residues on the inner wall of the equipment, and reduces residues, simplifies cleaning and maintenance, and reduces the number of residues in the inner wall of the equipment. Equipment loss and economic cost savings.

CN119391256AActive Publication Date: 2025-02-07TIANJIN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411500082.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively solve the problem of adhesion of residues of concrete machinery and equipment after use, resulting in the consolidation of the inner wall of the equipment, occupying space, affecting the output and transportation of materials, and a large amount of wastewater and waste are generated during the cleaning and maintenance process, resulting in equipment loss and Economic costs increase.

Method used

Using an efficient anti-adhesive agent, a hydrophobic and wear-resistant coating is formed by spraying on the inner wall of the tank of concrete mechanical equipment, reducing concrete material residues and simplifying cleaning and maintenance procedures. The anti-adhesive agent is prepared by emulsion polymerization, including an emulsifier, a hard segment monomer, a soft segment monomer, a fluorine-containing monomer and a silane coupling agent. It forms a homogeneous core-shell structure latex particles by phacoemulsification and initiator dropwise addition, and finally, it is possible to form a homogeneous core-shell structure latex particles. Add film-forming agent and silicone oil to dilute.

Benefits of technology

It effectively improves the hydrophobicity of the metal inner wall, reduces concrete material residues, simplifies cleaning and maintenance procedures, reduces equipment losses and wastewater waste generation, saves construction costs and improves economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391256A_ABST
    Figure CN119391256A_ABST
Patent Text Reader

Abstract

The invention relates to the field of concrete processing and mechanical equipment, in particular to an efficient anti-sticking agent applied to concrete mechanical equipment as well as a preparation method and application of the efficient anti-sticking agent. According to the preparation method, a polyacrylate coating is taken as a matrix, the coating is endowed with certain hydrophobic property by introducing a fluorine-containing functional monomer and a silane coupling agent, and the hardness and alkali resistance of the coating are further improved by introducing a rigid styrene monomer, so that the efficient anti-sticking agent with good hydrophobic property and excellent alkali resistance and wear resistance is prepared. A uniform coating can be formed when the coating is sprayed on the inner wall of a tank body of concrete mechanical equipment, the hydrophobicity of the metal inner wall can be effectively improved, residues of concrete materials after discharging are reduced, and the problems that due to excessive material residues, concrete mixing is uneven, and the yield and performance are reduced are solved; meanwhile, due to the existence of the coating, corrosion and abrasion of materials to the interior of the tank body in the concrete slurry mixing and transporting process can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete processing and mechanical equipment, and in particular to a high-efficiency anti-sticking agent applied to concrete mechanical equipment, and a preparation method and application thereof. Background Art

[0002] Modern commercial concrete is mainly produced by large-scale concrete mixing plants and transported to various construction sites by concrete mixer trucks. This production method can effectively improve the production efficiency and performance of concrete, while saving costs and reducing environmental pollution.

[0003] In actual application, after the materials are unloaded, there will still be some concrete material residue inside the mixing system, delivery pump and mixing truck of the mixing station, especially near the belt-shaped spiral blades. If it is not cleaned in time, the residual concrete will gradually solidify inside the tank, which will occupy the tank space, reduce the tank volume, reduce the material output and transportation volume; secondly, it will cause uneven mixing of concrete and affect the performance of concrete. In addition, for concrete mixer trucks, the gradually accumulated solidified materials will increase the weight of the mixing tank, increase the energy consumption of the vehicle, and accelerate the wear of vehicle tires, reducers and other components, leading to vehicle failure problems. At present, after the use of concrete machinery and equipment, construction personnel will use a large amount of water to flush the inside of the equipment and regularly clean the inside of the tank manually. However, a large amount of wastewater and waste will be generated during the cleaning and maintenance of the equipment, and the violent knocking and peeling during the regular maintenance process can easily cause irreversible damage to the tank. Therefore, if it is possible to control from the source, improve the stain resistance of the inner wall of concrete equipment, and reduce the residual concrete materials in the unloading stage, it can effectively ensure the output and quality of concrete materials, reduce the loss and maintenance of mechanical equipment and the output of wastewater and waste materials, which is of great significance in saving construction costs and improving economic benefits. At present, anti-adhesive agents and corresponding technologies for concrete machinery and equipment have not been reported. Summary of the invention

[0004] The purpose of the present invention is to provide a high-efficiency anti-sticking agent for concrete machinery and equipment and a preparation method and application thereof in view of the technical gaps in the prior art. The high-efficiency anti-sticking agent prepared by the method of the present invention can form a hydrophobic and wear-resistant coating on the surface of the metal inner wall after being sprayed on the inner wall of the tank of the concrete machinery and equipment, thereby effectively improving the hydrophobicity of the metal inner wall and reducing the residue of concrete materials in the tank.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a high-efficiency anti-sticking agent, comprising the following steps:

[0007] Dissolve the pH stabilizer and emulsifier in water and mix well to obtain a primer;

[0008] Adding emulsifier, hard segment monomer and soft segment monomer into water, and ultrasonically emulsifying to obtain pre-emulsified core monomer emulsion;

[0009] Adding an emulsifier, a hard segment monomer, a soft segment monomer, a fluorine-containing monomer and a silane coupling agent into water for ultrasonic emulsification to obtain a pre-emulsified shell monomer emulsion;

[0010] Adding the initiator into water and mixing well to obtain an initiator solution;

[0011] Heat the primer to 70-85°C, add part of the pre-emulsified core monomer emulsion, stir evenly, and then add 1 / 3 volume of the initiator solution to the reaction system;

[0012] After the free radical polymerization reaction of the core monomer in the system is triggered to form a seed emulsion and a blue light effect is exhibited, the remaining pre-emulsified core monomer emulsion and 1 / 3 volume of the initiator solution are added to the reaction system respectively, and then the system is kept warm (70-85°C for 30-50 minutes) to prepare a stable core emulsion with uniform and narrow particle size distribution;

[0013] The pre-emulsified shell monomer emulsion and 1 / 3 volume of the initiator solution are added to the reaction system respectively, and then the system is kept warm (70-85° C. for 60-120 min), so that the pre-emulsified shell monomer can continue to grow on the surface of the core latex particles, and a stable latex containing uniform core-shell structure latex particles is obtained;

[0014] The stable latex containing the uniform core-shell structure latex particles is diluted, and then a film-forming agent and silicone oil are added, and the mixture is stirred evenly to obtain a high-efficiency anti-sticking agent.

[0015] In the process of preparing a stable core latex having a uniform and narrow particle size distribution, and a stable latex containing uniform core-shell structure latex particles, the reaction temperature and reaction steps are set as above for the following reasons:

[0016] The reaction temperature of 70-85°C is to effectively trigger the free radical polymerization reaction of the monomers, and the reaction steps are set in this way to form a core-shell structure latex with uniform and stable particle size. Adjustment of the reaction steps, such as directly mixing the raw materials used to prepare the pre-emulsified core monomer emulsion and the pre-emulsified shell monomer emulsion together, will not result in latex particles with a core-shell structure; or, if the emulsified core monomer emulsion and 2 / 3 volume of the initiator solution are added to the primer together, the particle size and distribution of the latex particles will not be as uniform and stable as this method, and may even affect the stability of the subsequent synthesis addition.

[0017] In a preferred embodiment of the present invention, the mass ratio of the pH stabilizer to the emulsifier in the primer is 0.42:(0.56-0.90); the pH stabilizer is sodium bicarbonate; the emulsifier in the primer is one or two of fatty alcohol polyoxyethylene ether, OP-10 and sodium lauryl sulfate. In a more preferred embodiment of the present invention, the emulsifier in the primer is a mixture of fatty alcohol polyoxyethylene ether and sodium lauryl sulfate in a mass ratio of 1.25:1 to 1:2, or a mixture of OP-10 and sodium lauryl sulfate in a mass ratio of 1.25:1 to 1:2.

[0018] In a preferred embodiment of the present invention, the mass ratio of the emulsifier, the hard segment monomer and the soft segment monomer in the pre-emulsified core monomer emulsion is (1.11-1.80):(10.02-18.00):(9.00-15.06); the emulsifier in the pre-emulsified core monomer emulsion is one or two of fatty alcohol polyoxyethylene ether, OP-10 and sodium lauryl sulfate; in a more preferred embodiment of the present invention, the emulsifier in the pre-emulsified core monomer emulsion is a mixture of fatty alcohol polyoxyethylene ether and sodium lauryl sulfate in a mass ratio of 1.25:1 to 1:2, or a mixture of OP-10 and sodium lauryl sulfate in a mass ratio of 1.25:1 to 1:2. The hard segment monomer in the pre-emulsified core monomer emulsion is one or two of methyl methacrylate, ethyl methacrylate, and styrene (further preferably, when styrene and one of the acrylic ester monomers are used together, the mass ratio thereof is 1:1.5 to 2:1); the soft segment monomer in the pre-emulsified core monomer emulsion is one or two of n-butyl acrylate, isooctyl acrylate, and ethyl acrylate (further preferably, when two soft monomers are used together, the mass ratio of one of n-butyl acrylate / ethyl acrylate to isooctyl acrylate is 1:1 to 1.5:1).

[0019] In a preferred embodiment of the present invention, the mass ratio of the emulsifier, hard segment monomer, soft segment monomer, fluorine-containing monomer and silane coupling agent in the pre-emulsified shell monomer emulsion is (1.11-1.80):(10.02-18.00):(9.00-15.06):(3.40-5.40):(1.62-2.16g); the emulsifier in the pre-emulsified shell monomer emulsion is one or two of fatty alcohol polyoxyethylene ether, OP-10 and sodium dodecyl sulfate (when one of fatty alcohol polyoxyethylene ether and OP-10 is used with sodium dodecyl sulfate at the same time, the mass ratio is 1.25:1 to 1:2); the hard segment monomer in the pre-emulsified shell monomer emulsion is methyl methacrylate, ethyl methacrylate, styrene One or two of the following (when styrene and one of the acrylic ester monomers are used together, the mass ratio is 1:1.5 to 2:1); the soft segment monomer in the pre-emulsified shell monomer emulsion is one or two of n-butyl acrylate, isooctyl acrylate, and ethyl acrylate (when two soft monomers are used together, the mass ratio is 1:1 to 1.5:1); the fluorine-containing monomer in the pre-emulsified shell monomer emulsion is at least one of perfluorohexylethylene, dodecafluoroheptyl methacrylate, 2,2,2-trifluoroethyl methacrylate, or tridecafluorooctyl acrylate; the silane coupling agent in the pre-emulsified shell monomer emulsion is γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, or vinyltrimethoxysilane;

[0020] The initiator is ammonium persulfate, potassium persulfate or azobisisobutyramidine hydrochloride;

[0021] The film-forming aid is dipropylene glycol, propylene glycol butyl ether or dodecyl alcohol ester;

[0022] The silicone oil is dimethyl silicone oil or benzyl silicone oil.

[0023] In a preferred embodiment of the present invention, the mass ratio of the pH stabilizer in the primer to the emulsifier in the pre-emulsified core monomer emulsion, the emulsifier, initiator, film-forming agent and silicone oil in the pre-emulsified shell monomer emulsion is 0.42:(1.11-1.80):(1.11-1.80):(0.30-0.36):(0.5-1.0):(0.5-1.0).

[0024] In a preferred embodiment of the present invention, after a portion of the pre-emulsified core monomer emulsion is added to the primer solution and stirred evenly, 1 / 3 volume of the initiator solution is uniformly dripped into the reaction system at a dripping rate of 0.253 mL / min to 0.404 mL / min;

[0025] After the emulsion emits blue light, the remaining pre-emulsified core monomer emulsion and 1 / 3 volume of the initiator solution are added to the reaction system respectively, wherein the remaining pre-emulsified core monomer emulsion drop acceleration rate is 0.513 mL / min to 0.869 mL / min, and the initiator drop acceleration rate is 0.112 mL / min to 0.169 mL / min;

[0026] The pre-emulsified shell monomer emulsion and 1 / 3 volume of the initiator solution are respectively added into the reaction system, wherein the pre-emulsified shell monomer emulsion drop acceleration rate is 0.367 mL / min to 0.515 mL / min, and the initiator drop acceleration rate is 0.056 mL / min to 0.084 mL / min.

[0027] In each step, the drop acceleration rate of the pre-emulsified core / shell monomer emulsion will affect the stability of the final latex. If the drop acceleration rate of the pre-emulsified core / shell monomer emulsion is too slow, the pre-emulsion may break; if the drop acceleration rate is too fast, it will lead to incomplete reaction of the pre-emulsion, and even self-aggregation of the shell monomer latex particles, affecting the formation of core-shell structure latex particles.

[0028] Similarly, the initiator addition rate will also affect the stability of the final latex system and the uniformity of the latex particles. If the initiator addition rate is too slow, the particle size of the latex particles formed will be too large; if the addition rate is too fast, the reaction may proceed rapidly and cause explosion problems.

[0029] In a preferred embodiment of the present invention, the homogeneous latex is diluted with water to a solid content of 8% to 30%.

[0030] The second technical solution of the present invention is a high-efficiency anti-sticking agent prepared by the above-mentioned preparation method.

[0031] A third technical solution of the present invention is the use of the above-mentioned high-efficiency anti-sticking agent in mechanical equipment used in the preparation or transportation of commercial concrete.

[0032] The high-efficiency anti-sticking agent prepared by the present invention can be sprayed on the tank body of concrete machinery and equipment to effectively improve the hydrophobicity and stain resistance of the inner wall of the tank body, reduce material residue during concrete discharging, simplify equipment cleaning and maintenance procedures, alleviate equipment wear and failure problems, and improve the output, performance and economic benefits of commercial concrete.

[0033] The present invention discloses the following technical effects:

[0034] 1. The raw materials used in the preparation method of the present invention are widely available, and there are relatively mature industrial emulsion polymerization production processes and production equipment, which are easy for large-scale production and engineering applications.

[0035] 2. The present invention uses a polyacrylate coating with strong adhesion, not easy to fall off and good weather resistance as a matrix, and adjusts the hardness and adhesion of the coating by adjusting the ratio of soft and hard segments in the polymer; and introduces styrene monomer to further improve the hardness and alkali resistance of the coating; at the same time, fluorine-containing monomers and silane coupling agents are introduced into the polyacrylate coating to improve the hydrophobicity and wear resistance of the coating, so that the prepared high-efficiency anti-sticking agent used in concrete machinery and equipment has good adhesion, alkali resistance, wear resistance and hydrophobicity.

[0036] 3. The high-efficiency anti-sticking agent prepared by the present invention and applied to concrete machinery and equipment can form a hydrophobic and wear-resistant coating when sprayed on the inner wall of the tank of the concrete machinery and equipment, which can effectively improve the hydrophobicity of the metal inner wall, thereby reducing the residue of concrete materials after unloading. It can be cleaned up by flushing with a small amount of clean water, simplifying the subsequent cleaning and maintenance procedures, thereby reducing the problems of uneven concrete mixing, decreased output and performance caused by excessive concrete residues, and at the same time reducing the loss and maintenance of machinery and equipment and the output of wastewater and waste, saving a lot of economic costs.

[0037] 4. The coating formed by spraying the high-efficiency anti-sticking agent prepared by the present invention and applied to concrete machinery and equipment on the inner wall of the tank of the concrete machinery and equipment can reduce the corrosion and wear of the materials on the inside of the tank during concrete mixing and transportation, thereby increasing the service life of the machinery and equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 The figures show the wear conditions of tungsten steel plates sprayed with high-efficiency anti-sticking agents in different embodiments and comparative examples; wherein (a) is comparative example 1, (b) is embodiment 1, (c) is embodiment 2, (d) is embodiment 3, (e) is embodiment 4, and (f) is embodiment 5. DETAILED DESCRIPTION

[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0041] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0045] The "%" described in the present invention, unless otherwise specified, refers to mass percentage.

[0046] The present invention provides a method for preparing a high-efficiency anti-sticking agent for concrete machinery and equipment, comprising the following steps:

[0047] Step 1, dissolving 0.42 g of pH stabilizer and 0.56-0.90 g of emulsifier in 50 g of deionized water in order by mass, and stirring evenly to obtain a primer solution;

[0048] Step 2, adding 1.11-1.80 g of emulsifier, 10.02-18.00 g of hard segment monomer, and 9.00-15.06 g of soft segment monomer to 30 g of deionized water in order by mass, stirring evenly, and transferring to an ultrasonic cell pulverizer for ultrasonic emulsification for 30-50 min to obtain a pre-emulsified core monomer emulsion;

[0049] Step 3, adding 1.11-1.80 g of emulsifier, 10.02-18.00 g of hard segment monomer, 9.00-15.06 g of soft segment monomer, 3.40-5.40 g of fluorine-containing monomer and 1.62-2.16 g of silane coupling agent to 30 g of deionized water in order by mass, stirring evenly, transferring to an ultrasonic cell crusher for ultrasonic emulsification for 30-50 min, and obtaining a pre-emulsified shell monomer emulsion;

[0050] Step 4, adding 0.30-0.36 g of initiator to 30 g of deionized water, and stirring to obtain an initiator solution;

[0051] Step 5, heating the primer obtained in step 1 to 70-85°C, adding 10-15g of the pre-emulsified core monomer emulsion obtained in step 2, stirring for 10-20min, and then dripping 1 / 3 of the initiator solution obtained in step 4 into the reaction system for 25-40min;

[0052] Step 6, after the reaction emulsion in step 5 emits blue light, the remaining pre-emulsified core monomer emulsion obtained in step 2 and 1 / 3 of the initiator solution obtained in step 4 are dripped into the reaction system respectively, the dripping time is 50-90 minutes, and then the temperature is kept for 30-50 minutes;

[0053] Step 7, dripping the pre-emulsified shell monomer emulsion obtained in step 3 and 1 / 3 of the initiator solution obtained in step 4 into the reaction system respectively, the dripping time is 120-180 minutes, and then continuing to keep warm for 60-120 minutes to obtain a uniform emulsion;

[0054] Step 8, adding distilled water to dilute the uniform latex obtained in step 7 to a solid content of 8%-30%, and then adding 0.5-1.0g of film-forming agent and 0.5-1.0g of silicone oil, stirring evenly to obtain a high-efficiency anti-sticking agent for concrete machinery and equipment.

[0055] The high-efficiency anti-sticking agent prepared by the present invention is applied to concrete machinery and equipment, which can reduce the concrete residue in the machinery and equipment, reduce the internal wear of the equipment, the amount of water used for cleaning and the maintenance cost, effectively save the cost and transportation cost of commercial concrete, and has great application value and economic benefits.

[0056] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1

[0059] A method for preparing a high-efficiency anti-sticking agent for concrete machinery and equipment, comprising the following steps:

[0060] Step 1, dissolving 0.42g of sodium bicarbonate and 0.90g of emulsifier in 50g of deionized water in order by mass, and stirring evenly to obtain a primer, wherein the emulsifier is fatty alcohol polyoxyethylene ether and sodium lauryl sulfate, and the mass ratio thereof is 1.25:1;

[0061] Step 2, add 1.80g of emulsifier (1.0g of fatty alcohol polyoxyethylene ether + 0.80g of sodium lauryl sulfate), 17.04g of hard segment monomer (8.52g of methyl methacrylate + 8.52g of styrene), and 11.30g of soft segment monomer (5.80g of n-butyl acrylate + 5.5g of isooctyl acrylate) to 30g of deionized water in sequence by mass, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 40min, and obtain a pre-emulsified core monomer emulsion;

[0062] Step 3, add 1.80g of emulsifier (1.0g of fatty alcohol polyoxyethylene ether + 0.80g of sodium lauryl sulfate), 17.04g of hard segment monomer (8.52g of methyl methacrylate + 8.52g of styrene), 11.30g of soft segment monomer (5.80g of n-butyl acrylate + 5.5g of isooctyl acrylate), 4.54g of perfluorohexylethylene and 1.82g of vinyl triethoxysilane to 30g of deionized water in sequence by mass, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 40min, and obtain a pre-emulsified shell monomer emulsion;

[0063] Step 4, adding 0.36 g of ammonium persulfate to 30 g of deionized water, and stirring evenly to obtain an initiator solution;

[0064] Step 5, heating the primer obtained in step 1 to 85° C., adding 12 g of the pre-emulsified core monomer emulsion obtained in step 2, stirring for 15 min, and then dripping 1 / 3 (volume) of the initiator solution obtained in step 4 into the reaction system at a dripping rate of 0.337 mL / min;

[0065] Step 6, after the reaction system in step 5 shows blue light, the remaining pre-emulsified core monomer emulsion obtained in step 2 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the remaining pre-emulsified core monomer emulsion dripping rate is 0.802 mL / min, the initiator dripping rate is 0.168 mL / min, and then the temperature is kept for 40 minutes;

[0066] Step 7, the pre-emulsified shell monomer emulsion obtained in step 3 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the pre-emulsified shell monomer emulsion dripping rate is 0.443 mL / min, the initiator dripping rate is 0.067 mL / min, and then the temperature is kept for 90 minutes to obtain a uniform latex;

[0067] Step 8, adding distilled water to dilute the uniform latex obtained in step 7 to a solid content of 10%, and then adding 0.6g of dipropylene glycol and 0.6g of dimethyl silicone oil, stirring evenly to obtain a high-efficiency anti-sticking agent for concrete machinery and equipment.

[0068] Example 2

[0069] A method for preparing a high-efficiency anti-sticking agent for concrete machinery and equipment, comprising the following steps:

[0070] Step 1, dissolving 0.42 g of sodium bicarbonate and 0.56 g of an emulsifier in 50 g of deionized water in order by mass, and stirring evenly to obtain a primer, wherein the emulsifier is fatty alcohol polyoxyethylene ether and sodium lauryl sulfate, and the mass ratio thereof is 1:2;

[0071] Step 2, add 1.11g of emulsifier (0.37g of fatty alcohol polyoxyethylene ether + 0.74g of sodium lauryl sulfate), 10.02g of hard segment monomer (methyl methacrylate), and 15.06 of soft segment monomer (7.53g of ethyl acrylate + 7.53g of isooctyl acrylate) to 30g of deionized water in sequence by mass, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 30min, and obtain a pre-emulsified core monomer emulsion;

[0072] Step 3, add 1.11g of emulsifier (0.37g of fatty alcohol polyoxyethylene ether + 0.74g of sodium lauryl sulfate), 10.02g of hard segment monomer (methyl methacrylate), 15.06g of soft segment monomer (7.53g of ethyl acrylate + 7.53g of isooctyl acrylate), 4.00g of dodecafluoroheptyl methacrylate and 1.62g of γ-methacryloxypropyltrimethoxysilane to 30g of deionized water in order by mass, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 30min, and obtain a pre-emulsified shell monomer emulsion;

[0073] Step 4, adding 0.30 g of potassium persulfate into 30 g of deionized water, and stirring evenly to obtain an initiator solution;

[0074] Step 5, heating the primer obtained in step 1 to 80°C, adding 10 g of the pre-emulsified core monomer emulsion obtained in step 2, stirring for 10 min, and then dripping 1 / 3 of the initiator solution obtained in step 4 into the reaction system at a dripping rate of 0.404 mL / min;

[0075] Step 6, after the reaction system in step 5 appears blue light, the remaining pre-emulsified core monomer emulsion obtained in step 2 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the remaining pre-emulsified core monomer emulsion dripping rate is 0.513 mL / min, the initiator dripping rate is 0.112 mL / min, and then continue to keep warm for 30 minutes;

[0076] Step 7, the pre-emulsified shell monomer emulsion obtained in step 3 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the pre-emulsified shell monomer emulsion dripping rate is 0.513 mL / min, the initiator dripping rate is 0.084 mL / min, and then the temperature is kept for 120 minutes to obtain a uniform latex;

[0077] Step 8, adding distilled water to dilute the uniform latex obtained in step 7 to a solid content of 8%, and then adding 0.5g of dipropylene glycol and 0.5g of benzyl silicone oil, stirring evenly to obtain a high-efficiency anti-sticking agent for concrete machinery and equipment.

[0078] Example 3

[0079] A method for preparing a high-efficiency anti-sticking agent for concrete machinery and equipment, comprising the following steps:

[0080] Step 1, dissolving 0.42 g of sodium bicarbonate and 0.72 g of emulsifier in 50 g of deionized water in order by mass, and stirring evenly to obtain a primer, wherein the emulsifier is OP-10 and sodium dodecyl sulfate, and the mass ratio thereof is 1:1;

[0081] Step 2, add 1.44g of emulsifier (0.72g OP-10+0.72g of sodium dodecyl sulfate), 18g of hard segment monomer (styrene), and 9g of soft segment monomer (5.4g of n-butyl acrylate+3.60g of isooctyl acrylate) to 30g of deionized water in order by mass, stir evenly, transfer to an ultrasonic cell pulverizer and ultrasonically emulsify for 50min to obtain a pre-emulsified core monomer emulsion;

[0082] Step 3, adding 1.44 g of emulsifier (0.72 g of OP-10 + 0.72 g of sodium dodecyl sulfate), 18 g of hard segment monomer (styrene), 9 g of soft segment monomer (5.4 g of n-butyl acrylate + 3.60 g of isooctyl acrylate), 5.40 g of 2,2,2-trifluoroethyl methacrylate and 2.16 g of vinyltrimethoxysilane to 30 g of deionized water in sequence according to mass, stirring evenly, transferring to an ultrasonic cell pulverizer for ultrasonic emulsification for 50 min, and obtaining a pre-emulsified shell monomer emulsion;

[0083] Step 4, adding 0.32 g of azobisisobutylamidine hydrochloride to 30 g of deionized water, and stirring evenly to obtain an initiator solution;

[0084] Step 5, heating the primer obtained in step 1 to 70° C., adding 15 g of the pre-emulsified core monomer emulsion obtained in step 2, stirring for 20 min, and then dripping 1 / 3 of the initiator solution obtained in step 4 into the reaction system at a dripping rate of 0.253 mL / min;

[0085] Step 6, after the reaction system in step 5 appears blue light, the remaining pre-emulsified core monomer emulsion obtained in step 2 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the remaining pre-emulsified core monomer emulsion dripping rate is 0.869 mL / min, the initiator dripping rate is 0.202 mL / min, and then the temperature is kept for 50 minutes;

[0086] Step 7, the pre-emulsified shell monomer emulsion obtained in step 3 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the pre-emulsified shell monomer emulsion dripping rate is 0.367 mL / min, the initiator dripping rate is 0.056 mL / min, and then the temperature is kept for 60 minutes to obtain a uniform latex;

[0087] Step 8, adding distilled water to dilute the uniform latex obtained in step 7 to a solid content of 30%, and then adding 1.0g of dodecyl alcohol ester and 1.0g of benzyl silicone oil, stirring evenly to obtain a high-efficiency anti-sticking agent for concrete machinery and equipment.

[0088] Example 4

[0089] A method for preparing a high-efficiency anti-sticking agent for concrete machinery and equipment, comprising the following steps:

[0090] Step 1, dissolving 0.42 g of sodium bicarbonate and 0.60 g of sodium dodecyl sulfate in 50 g of deionized water in order by mass, and stirring evenly to obtain a primer solution;

[0091] Step 2, add 1.20g of sodium dodecyl sulfate, 14.20g of hard segment monomer (8.52g of ethyl methacrylate + 5.68g of styrene), and 14.50g of soft segment monomer (isooctyl acrylate) to 30g of deionized water in order by mass, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 30min, and obtain a pre-emulsified core monomer emulsion;

[0092] Step 3, in order by mass, add 1.20 g of sodium dodecyl sulfate, 14.20 g of hard segment monomer (8.52 g of ethyl methacrylate + 5.68 g of styrene), 14.50 g of soft segment monomer (isooctyl acrylate), 4.54 g of tridecafluorooctyl acrylate and 1.82 g of vinyl triisopropyl silane to 30 g of deionized water, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 30 min, and obtain a pre-emulsified shell monomer emulsion;

[0093] Step 4, adding 0.32 g of ammonium persulfate to 30 g of deionized water, and stirring evenly to obtain an initiator solution;

[0094] Step 5, heating the primer obtained in step 1 to 82° C., adding 12 g of the pre-emulsified core monomer emulsion obtained in step 2, stirring for 20 min, and then dripping 1 / 3 of the initiator solution obtained in step 4 into the reaction system at a dripping rate of 0.253 mL / min;

[0095] Step 6, after the reaction system in step 5 appears blue light, the remaining pre-emulsified core monomer emulsion obtained in step 2 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the remaining pre-emulsified core monomer emulsion dripping rate is 0.684 mL / min, the initiator dripping rate is 0.144 mL / min, and then the temperature is kept for 40 minutes;

[0096] Step 7, the pre-emulsified shell monomer emulsion obtained in step 3 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the pre-emulsified shell monomer emulsion dripping rate is 0.442 mL / min, the initiator dripping rate is 0.067 mL / min, and then the temperature is kept for 90 minutes to obtain a uniform latex;

[0097] Step 8, adding distilled water to dilute the uniform latex obtained in step 7 to a solid content of 20%, and then adding 0.8g of propylene glycol butyl ether and 0.8g of benzyl silicone oil, stirring evenly to obtain a high-efficiency anti-sticking agent for concrete machinery and equipment.

[0098] Example 5

[0099] A method for preparing a high-efficiency anti-sticking agent for concrete machinery and equipment, comprising the following steps:

[0100] Step 1, dissolving 0.42 g of sodium bicarbonate and 0.72 g of fatty alcohol polyoxyethylene ether in 50 g of deionized water in order by mass, and stirring evenly to obtain a primer solution;

[0101] Step 2, add 1.44g fatty alcohol polyoxyethylene ether, 20.00g hard segment monomer (6.66g methyl methacrylate + 13.34g styrene), and 10g soft segment monomer (n-butyl acrylate) to 30g deionized water in order by mass, stir evenly, transfer to an ultrasonic cell crusher for ultrasonic emulsification for 40min, and obtain a pre-emulsified core monomer emulsion;

[0102] Step 3, adding 1.44g of fatty alcohol polyoxyethylene ether, 20.00g of hard segment monomer (6.66g of methyl methacrylate + 13.34g of styrene), 10g of soft segment monomer (n-butyl acrylate), 3.40g of perfluorohexylethylene and 1.70g of vinyl triethoxysilane to 30g of deionized water in step 2 in sequence by mass, stirring evenly, transferring to an ultrasonic cell crusher for ultrasonic emulsification for 40min, and obtaining a pre-emulsified shell monomer emulsion;

[0103] Step 4, adding 0.36 g of ammonium persulfate to 30 g of deionized water, and stirring evenly to obtain an initiator solution;

[0104] Step 5, heating the primer obtained in step 1 to 85°C, adding 15 g of the pre-emulsified core monomer emulsion obtained in step 2, stirring for 20 min, and then dripping 1 / 3 of the initiator solution obtained in step 4 into the reaction system at a dripping rate of 0.253 mL / min;

[0105] Step 6, after the reaction system in step 5 appears blue light, the remaining pre-emulsified core monomer emulsion obtained in step 2 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the remaining pre-emulsified core monomer emulsion dripping rate is 0.744 mL / min, the initiator dripping rate is 0.169 mL / min, and then the temperature is kept for 30 minutes;

[0106] Step 7, the pre-emulsified shell monomer emulsion obtained in step 3 and 1 / 3 of the initiator solution obtained in step 4 are respectively dripped into the reaction system, the pre-emulsified shell monomer emulsion dripping rate is 0.444 mL / min, the initiator dripping rate is 0.067 mL / min, and then the temperature is kept for 90 minutes to obtain a uniform latex;

[0107] Step 8, adding distilled water to dilute the uniform latex obtained in step 7 to a solid content of 10%, and then adding 0.6g of dipropylene glycol and 0.6g of dimethyl silicone oil, stirring evenly to obtain a high-efficiency anti-sticking agent for concrete machinery and equipment.

[0108] Comparative Example 1

[0109] Commercially available anti-adhesive agent sample A was purchased from Shandong Anrui, model number Fuxun concrete anti-adhesive agent.

[0110] In order to verify the hydrophobic modification effect of the high-efficiency anti-sticking agent (hereinafter referred to as the high-efficiency anti-sticking agent) applied to concrete machinery and equipment of the present invention on the inner wall of the tank of concrete machinery and equipment, tungsten steel plate, a common material for tank bodies, was selected as the substrate, and the anti-sticking agent sample A in comparative example 1 and the high-efficiency anti-sticking agents prepared in Examples 1, 2, 3, 4, and 5 were uniformly sprayed on the clean surface of the tungsten steel plate through a spraying device, and placed at room temperature to dry for 24 hours, and tested and compared after film formation.

[0111] First, the contact angle test was carried out on the cleaned tungsten steel plate substrate, the tungsten steel plate of spray comparison example 1, the tungsten steel plate of spray example 1, the tungsten steel plate of spray example 2, the tungsten steel plate of spray example 3, the tungsten steel plate of spray example 3, the tungsten steel plate of spray example 4, and the tungsten steel plate of spray example 5. The test results are shown in Table 1.

[0112] Table 1 Contact angle of tungsten steel plate before and after treatment with high-efficiency anti-adhesive sample

[0113]

[0114] It can be seen from the test results that the contact angle of the tungsten steel plate substrate surface is 88°, and it is not hydrophobic; after spraying the anti-sticking agent sample A of comparative example 1 and the high-efficiency anti-sticking agent prepared in Examples 1, 2, 3, 4, and 5 on the substrate surface, the contact angle of the tungsten steel plate surface is greater than 90°, confirming that the anti-sticking agent sample A and the high-efficiency anti-sticking agent prepared in Examples 1, 2, 3, 4, and 5 can give the surface of cement machinery and equipment a certain hydrophobicity and reduce material residue during unloading.

[0115] Then, several tungsten steel plates with coatings were immersed in 15% sodium hydroxide solution for a specified time, and then the tungsten steel plates were taken out, cleaned and dried, and the surface contact angle was tested. The alkali resistance of the anti-adhesive sample A in comparative example 1 and the high-efficiency anti-adhesive prepared in examples 1, 2, 3, 4, and 5 was evaluated by monitoring the change of the surface contact angle of the tungsten steel plate after immersion for different times. The test results are shown in Table 2.

[0116] Table 2 Changes in contact angle of tungsten steel plate after immersion in 15% sodium hydroxide

[0117]

[0118] It can be seen from Table 2 that the surface contact angle of the tungsten steel plate sprayed with the anti-adhesive sample A in comparative example 1 decreases with the increase of the soaking time in the alkali solution. After soaking for 195 minutes, the surface contact angle of the tungsten steel plate is 89°, which is 25.8% lower than the initial value. However, the several tungsten steel plates sprayed with the high-efficiency anti-adhesive prepared in Examples 1, 2, 3, 4, and 5 of the present invention can maintain excellent hydrophobicity after soaking in the alkali solution for 195 minutes, and the contact angle decreases by no more than 6%, which proves that the high-efficiency anti-adhesive in the present invention has good alkali resistance, can resist the long-term alkaline erosion of cement materials, and prolong the service life of the coating.

[0119] Subsequently, the wear resistance of several tungsten steel plate surface coatings was tested using a wear tester. The test method is as follows: the coated tungsten steel plate is fixed in the wear tester fixture, and then the grinding head of the tester is coated with glass wool (0000 specification, produced by Japan BON STAR Company) and a 1kg weight is placed, and then the grinding head is lowered and the tester is started, and the grinding head is linearly reciprocated on the coating surface for 50 times, and then removed to observe the wear of the coating on the tungsten steel plate surface. Figure 1 The wear conditions of the tungsten steel plate of spraying comparative example 1, the tungsten steel plate of spraying example 1, the tungsten steel plate of spraying example 2, the tungsten steel plate of spraying example 3, the tungsten steel plate of spraying example 4, and the tungsten steel plate of spraying example 5 are listed respectively. Figure 1 It can be seen in (a) that after 50 times of linear reciprocating friction, a large area of ​​bright silver appears in the test area of ​​the tungsten steel plate sprayed with the anti-sticking agent sample A of comparative example 1, and the coating is worn a lot, indicating that the coating formed by the anti-sticking agent sample A of comparative example 1 has poor wear resistance. Figure 1 (b) shows that after 50 times of linear reciprocating friction, the tungsten steel plate sprayed with the high-efficiency anti-sticking agent prepared in Example 1 has only a very small bright silver area, and the coating can be completely retained, which proves that the high-efficiency anti-sticking agent prepared in Example 1 has good alkali resistance. The tungsten steel plate sprayed with the high-efficiency anti-sticking agent prepared in Example 2 has a slightly increased bright silver area after 50 times of linear reciprocating friction. This is because the prepared high-efficiency anti-sticking agent does not contain styrene, resulting in a slight decrease in the hardness and wear resistance of the coating, but it is still higher than that of Comparative Example 1. The high-efficiency anti-sticking agent prepared in Example 3 contains a large amount of styrene, which increases the hardness of the coating but has a negative impact on the adhesion of the coating. Therefore, the tungsten steel plate sprayed with Example 3 also has a certain bright silver area after the wear resistance test ( Figure 1 (d)), but the coating coverage area is also higher than that of Comparative Example 1. The wear resistance of the tungsten steel plates sprayed with the high-efficiency anti-sticking agents prepared in Examples 4 and 5 after 50 linear reciprocating frictions is similar to that of Example 1, among which the wear resistance of the high-efficiency anti-sticking agent prepared in Example 4 is slightly inferior to that of Examples 1 and 5.

[0120] Based on the above experimental results, compared with the anti-sticking agent sample A in comparative example 1, the high-efficiency anti-sticking agent prepared in the present invention has good alkali resistance and wear resistance while imparting hydrophobicity to the metal substrate, and can effectively resist the alkaline corrosion of cement materials during service, and reduce the wear of solid phase particles on the inner wall of the tank body, thereby reducing the residual cement material while ensuring the service life of the coating and mechanical equipment.

[0121] The high-efficiency anti-adhesive agent applied to concrete machinery and equipment of the present invention has the characteristics of wide raw material sources, mature production process and equipment, and easy large-scale industrial production. The present invention uses polyacrylate coating as a matrix, introduces fluorine-containing functional monomers and silane coupling agents to give the coating a certain hydrophobic property, and further improves the hardness and alkali resistance of the coating by introducing rigid styrene monomers, so as to prepare a high-efficiency anti-adhesive agent with good hydrophobic properties and excellent alkali resistance and wear resistance. It can be sprayed on the inner wall of the tank of concrete machinery and equipment to form a uniform coating, which can effectively improve the hydrophobicity of the metal inner wall, reduce the residue of concrete materials after unloading, and avoid problems such as uneven concrete mixing, reduced output and performance caused by excessive material residues; at the same time, the presence of the coating can reduce the corrosion and wear of materials on the inside of the tank during concrete mixing and transportation, and the mechanical equipment after use can be cleaned up under a small amount of clean water, simplifying the subsequent cleaning and maintenance procedures, reducing the output of wastewater and waste materials and the loss and maintenance of mechanical equipment, and saving a lot of economic costs.

[0122] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a high-efficiency anti-adhesive agent, characterized in that: The following steps are involved: Dissolve the pH stabilizer and emulsifier in water and mix well to obtain a primer; Adding emulsifier, hard segment monomer and soft segment monomer into water, and ultrasonically emulsifying to obtain pre-emulsified core monomer emulsion; Adding an emulsifier, a hard segment monomer, a soft segment monomer, a fluorine-containing monomer and a silane coupling agent into water for ultrasonic emulsification to obtain a pre-emulsified shell monomer emulsion; Adding the initiator into water and mixing well to obtain an initiator solution; Heat the primer to 70-85°C, add part of the pre-emulsified core monomer emulsion into it, stir evenly, and then add 1 / 3 volume of the initiator solution into the reaction system; after the free radical polymerization reaction of the core monomer in the system is triggered to form a seed emulsion, and the emulsion shows a blue light effect, add the remaining pre-emulsified core monomer emulsion and 1 / 3 volume of the initiator solution into the reaction system respectively and continue to keep warm at 70-85°C for 30-50 minutes; The pre-emulsified shell monomer emulsion and 1 / 3 volume of the initiator solution are added to the reaction system respectively, and then the temperature is kept at 70-85°C for 60-120 minutes to obtain a stable latex containing uniform core-shell structure latex particles; The stable latex containing the uniform core-shell structure latex particles is diluted, and then a film-forming agent and silicone oil are added, and the mixture is stirred evenly to obtain a high-efficiency anti-sticking agent.

2. The method for preparing a high-efficiency anti-adhesive agent according to claim 1, characterized in that: The mass ratio of the pH stabilizer to the emulsifier in the primer is 0.42:(0.56-0.90); the pH stabilizer is sodium bicarbonate; the emulsifier in the primer is one or two of fatty alcohol polyoxyethylene ether, OP-10 and sodium lauryl sulfate.

3. The method for preparing a high-efficiency anti-adhesive agent according to claim 1, characterized in that: The mass ratio of the emulsifier, the hard segment monomer and the soft segment monomer in the pre-emulsified core monomer emulsion is (1.11-1.80):(10.02-18.00):(9.00-15.06); the emulsifier in the pre-emulsified core monomer emulsion is one or two of fatty alcohol polyoxyethylene ether, OP-10 and sodium dodecyl sulfate; the hard segment monomer in the pre-emulsified core monomer emulsion is one or two of methyl methacrylate, ethyl methacrylate and styrene; the soft segment monomer in the pre-emulsified core monomer emulsion is one or two of n-butyl acrylate, isooctyl acrylate and ethyl acrylate.

4. The method for preparing a high-efficiency anti-adhesive agent according to claim 1, characterized in that: The mass ratio of the emulsifier, hard segment monomer, soft segment monomer, fluorine-containing monomer and silane coupling agent in the pre-emulsified shell monomer emulsion is (1.11-1.80):(10.02-18.00):(9.00-15.06):(3.40-5.40):(1.62-2.16g); the emulsifier in the pre-emulsified shell monomer emulsion is one or two of fatty alcohol polyoxyethylene ether, OP-10 and sodium dodecyl sulfate; the hard segment monomer in the pre-emulsified shell monomer emulsion is methyl methacrylate, One or two of ethyl methacrylate and styrene; the soft segment monomer in the pre-emulsified shell monomer emulsion is one or two of n-butyl acrylate, isooctyl acrylate and ethyl acrylate; the fluorine-containing monomer is at least one of perfluorohexylethylene, dodecafluoroheptyl methacrylate, 2,2,2-trifluoroethyl methacrylate or tridecafluorooctyl acrylate; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane or vinyltrimethoxysilane; The initiator is ammonium persulfate, potassium persulfate or azobisisobutyramidine hydrochloride; The film-forming aid is dipropylene glycol, propylene glycol butyl ether or dodecyl alcohol ester; The silicone oil is dimethyl silicone oil or benzyl silicone oil.

5. The method for preparing a high-efficiency anti-adhesive agent according to claim 1, characterized in that: The mass ratio of the pH stabilizer to the emulsifier in the pre-emulsified core monomer emulsion, the emulsifier in the pre-emulsified shell monomer emulsion, the initiator, the film-forming agent, and the silicone oil is 0.42:(1.11-1.80):(1.11-1.80):(0.30-0.36):(0.5-1.0):(0.5-1.0).

6. The method for preparing a high-efficiency anti-adhesive agent according to claim 1, characterized in that: After adding part of the pre-emulsified core monomer emulsion into the primer solution and stirring evenly, 1 / 3 volume of the initiator solution is uniformly dripped into the reaction system at a dripping rate of 0.253 mL / min to 0.404 mL / min; After the emulsion emits blue light, the remaining pre-emulsified core monomer emulsion and 1 / 3 volume of the initiator solution are added to the reaction system respectively, wherein the remaining pre-emulsified core monomer emulsion drop acceleration rate is 0.513 mL / min to 0.869 mL / min, and the initiator drop acceleration rate is 0.112 mL / min to 0.169 mL / min; The pre-emulsified shell monomer emulsion and 1 / 3 volume of the initiator solution are respectively added into the reaction system, wherein the pre-emulsified shell monomer emulsion drop acceleration rate is 0.367 mL / min to 0.515 mL / min, and the initiator drop acceleration rate is 0.056 mL / min to 0.084 mL / min.

7. The method for preparing a high-efficiency anti-adhesive agent according to claim 1, characterized in that: The stable latex containing uniform core-shell structure latex particles is diluted to a solid content of 8%-30%.

8. A high-efficiency anti-sticking agent prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the high-efficiency anti-adhesive agent as claimed in claim 8 in mechanical equipment used in the preparation or transportation of commercial concrete.

Citation Information

Patent Citations

  • Styrene-acrylate emulsion with hydrophobic oleophylic fluorine-silicon-modified nuclear shell structure and preparation method thereof

    CN102060952A

  • Fluorosilicone-modified polyacrylate emulsion as well as preparing method and application thereof

    CN106519126A

  • Low surface energy coating and preparation method thereof

    CN108841322A

  • Preparation method and application of novel concrete release agent

    CN109294716A